Transabdominal pre-peritoneal repair procedure (TAPP) versus open hernia repair (OHR) in the treatment of inguinal hernia - Victor Dumitrescu; Dan Dumitrescu; Paul Lorin Stoica; George Draghici; Alexandru Chirca (Journal of Mind and Medical Sciences)
Inguinal hernia is a common condition, with about 30% of men and 6% of women developing this condition throughout their lifetime. Laparoscopic hernia repair procedures have become more and more important lately, due to the advantages of a fast recovery and reduced postoperative pain. The paper presents our clinical experience involving the TAPP repair procedure, compared to open hernia repair (OHR). We retrospectively compared our first 50 cases comprising patients who underwent the TAPP hernia repair procedure between January 2018 and June 2020, with 50 cases who underwent the OHR procedure in the same period. The total operation duration was 102.5 minutes in the TAPP group and 78.4 minutes in the OHR group. The average hospital stay in the TAPP group was 1.5 days with six patients requiring reinterventions for postoperative bleeding and who were discharged seven to nine days later. There is still no consensus regarding the use of tacks and/or the surgical glue, the surgeon's experience and the intraoperative findings representing a cornerstone in choosing the best repair method for each case. Laparoscopic hernia repair has some advantages over the open technique, but it can be followed by complications that can further raise parameters.